PENERAPAN METODE AR-RABITH DALAM PEMBELAJARAN TAHFIZHUL QUR’AN DI MIT IBNU MAS’UD YOGYAKARTA - Nusyaibah; Fu’ad Arif Noor (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
In the process of learning the Qur'an requires a method that is expected to facilitate the learning process. Learning Tahfizh Al-Qur'an at MIT Ibnu Mas'ud Yogyakarta uses the Ar-Rabith method which makes it easier for students to memorize the Qur'an. The peculiarity of the Ar-Rabith method in learning the Qur'an is a distinct advantage and value in Madrasah Ibtidaiyah because it is still rare for schools to apply the Tahfizh Al-Qur'an method. The problems in this study: (1) how the application of the Ar-Rabith method was carried out at MIT Ibnu Mas'ud Yogyakarta (2) what were the supporting and inhibiting factors in learning the Qur'an (3) what were the results of the application of the Ar-Rabith method in learning Al-Qur'an. While the aim is to describe and analyze the application, process and inhibiting and supporting factors in the application of Tahfizh learning using the Ar-Rabith method at MIT Ibnu Mas'ud Yogyakarta. This study used descriptive qualitative method. Data collection techniques using the method of observation, interviews and documentation. The results of the research conducted indicate that the Ar-Rabith Method is a method of binding memorization which is expected to continue to assist students in memorizing new memorization with the old. The supporting factors are motivation, a supportive environment, competent teachers and cooperation between schools and parents. The inhibiting factor is the ability of students below the standard, a sense of laziness in students and not all parents can be good motivators. The result is that the Ar-Rabith method was successfully applied according to the results of the researcher's interviews with teachers and students.